Olfactory Results of Endoscopic Endonasal Surgery for Pituitary Adenoma: A Prospective Study of 143 Patients - Netuka, David; Masopust, Václav; Fundová, Petra; Astl, Jaromír; Školoudík, David; Májovský, Martin; Beneš, Vladimír (World neurosurgery, 2019)
BACKGROUND: Clinical examination, including pre- and postoperative assessment of olfaction function, should be included in evaluating surgical outcomes in patients with pituitary adenomas. Most of the studies are lacking assessment of olfactory function. METHODS: A prospective study of 143 patients who underwent surgical resection of pituitary adenomas from January 2014 to December 2017 was performed. Data on clinical presentation, pre- and postoperative neurologic, endocrinologic, and ophthalmologic examinations, complications, and follow-up outpatient examinations were recorded. Olfactory function was assessed using the Sniffin' Sticks odor identification test preoperatively, postoperatively (3 months), and 1 year after surgery. RESULTS: Normosmia was present preoperatively in 93.7% of patients, postoperatively in 95.8% of patients, and in 95.1% 1 year postsurgery. Hyposmia was present preoperatively in 4.2% of patients, postoperatively in 2.1% of patients, and in 1.4% 1 year after surgery. Anosmia was present preoperatively in 2.1% of patients, postoperatively in 2.1% of patients, and in 3.5% 1 year after surgery. In patients with preoperative normosmia, postoperative hyposmia and anosmia were present in 1.5% of patients. There were no differences according to age, sex, size, or type of pituitary adenoma. CONCLUSIONS: Assessment of olfactory function should be included in the analysis of pituitary adenoma surgery results. This prospective study showed low risk of olfaction deterioration if an endoscopic endonasal approach is used without any mucosal flaps for skull base reconstruction. Further studies that include objective olfaction assessment are warranted.
Keywords: Young Adult; Olfaction Disorders; poruchy čichu; Male; Postoperative Complications; Neuroendoscopy; Transsphenoidal surgery; Pituitary adenoma; Olfactory function; mladý dospělý; Adolescent; Pituitary Neoplasms; Olfaction; Adult; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; pooperační komplikace; Natural Orifice Endoscopic Surgery; endoskopické operace přirozenými otvory; mladiství; Nose; Endoscopic endonasal approach; nádory hypofýzy; lidé; neuroendoskopie; ženské pohlaví; Humans; nos; Adenoma; adenom; Female; lidé středního věku; Middle Aged; prospektivní studie